What’s the effectiveness of stocking actions in small creeks? The role of water discharge behind hatchery trout downstream movement - Brignone, Stefano; De Santis, Vanessa; Putelli, Tiziano; Molina, Christophe; Piccinini, Armando; Carmichael, Richard A.; Volta, Pietro (PeerJ, 2022)
Fish stocking to enhance freshwater fisheries or to improve the conservation status of endangered fish species is a common practice in many countries. Little is known, however, of the effectiveness of these practices in spite of the high efforts and investments required. The movement of subadult/adult hatchery-released brown trout Salmo trutta L. was studied by passive telemetry in a small tributary of Lake Lugano (i.e., Laveggio Creek, Canton Ticino, Switzerland). Hatchery fish, together with some resident wild individuals sampled during electrofishing surveys, were tagged with Passive Integrated Transponders (PIT) tags. Hatchery fish were released upstream and downstream a submersible monitoring antenna, which was anchored to the streambed in a pass-over orientation. The number of hatchery fish detected daily by the antenna (divided between fish released upstream and downstream the antenna) was analyzed in relation to the daily water discharge, to search for similar patterns in their fluctuation over time. Only the movement of fish released upstream the antenna displayed a significant relationship with water discharge, with the highest number of fish detected during periods of high-water flow, occurring after heavy rains. High-water discharge events had a significant role in hatchery trout downstream movement in our study site, likely acting as a driver for the downstream migration to Lake Lugano. Such events contributed to the poor effectiveness of stocking actions in this small tributary, providing further evidence against stocking strategies based on subadult/adult fish.
Keywords: Fish stocking; Stock enhancement; Passive integrated transponder (PIT); Fish telemetry; Fish movement; Brown trout